2020
DOI: 10.14639/0392-100x-n0538
|View full text |Cite
|
Sign up to set email alerts
|

Platysma myocutaneous flap revised in the free flaps era: clinical experience in 61 patients

Abstract: Tecnica alternativa per il prelievo del lembo di platisma miocutaneo nell'era dei lembi liberi: esperienza clinica in 61 pazienti

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
1
4
0
1
Order By: Relevance
“…Moreover, multivariable analyses (adjusted for prognostic and confounding factors) showed that OTSCC survival and prognosis in patients treated with CTS were not related to the single center. These data confirmed that the anatomically based approach of CTS is a highly reproducible surgical technique and can be codified by already published surgical steps based on tongue and floor of the mouth anatomy 15,34 …”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Moreover, multivariable analyses (adjusted for prognostic and confounding factors) showed that OTSCC survival and prognosis in patients treated with CTS were not related to the single center. These data confirmed that the anatomically based approach of CTS is a highly reproducible surgical technique and can be codified by already published surgical steps based on tongue and floor of the mouth anatomy 15,34 …”
Section: Discussionsupporting
confidence: 73%
“…These data confirmed that the anatomically based approach of CTS is a highly reproducible surgical technique and can be codified by already published surgical steps based on tongue and floor of the mouth anatomy. 15,34 Focusing on functional results of patients treated with CTS, removing the lingual extrinsic muscles from their bone insertion could result in a larger excision than the SWMS, but as already reported in some published works on this topic, a dissected muscle does not maintain functionality and, a good reconstruction fills the excision gap. 13 It is already reported that CTS could offer superior oncologic results without reducing functional outcomes compared with SWMS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, they found that even superficial thin tumors can involve these muscles, and high rates of invasion of these three muscles (hyoglossus, 95%; styloglossus, 93.6%; genioglossus, 53.2%) at DOIs >10 mm were reported. To achieve radical oncologic resection, compartmental surgery 17 or pull‐through resection of the T‐N tract 18 en bloc is performed. Therefore, in T3 and above, a skin incision is made in the neck, and elective ND is often indicated for tumor control and surgical necessity at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…Su evolución dentro del campo quirúrgico maxilofacial ha evolucionado mucho; sin embargo, son muchas las controversias que aún se generan con su uso. [1][2][3]…”
Section: Introductionunclassified